Developing Science Learning through a Hydroponics Project to Improve Students’ Science Literacy Skills - Rohmawati, Laili; Zen, Salsa Bila; Aulia, Suci; Fattahillah, Nuris (Gemilang Maju Publikasi Ilmiah (GMPI), 2026)
The purpose of this study was to build science learning based on a hydroponic project as an effort to enhance junior high school student’s scientific literacy in Banten Province. A descriptive quantitative design included thirteen ninth grade students. Scientific literacy was measured during pre-test/post-test, which was reinforced with engagement and attitudes towards science observation. Results demonstrated significant increases in average scores from 66.92 to 95.38 and an average improvement of 44.2%. Learners with low pre-knowledge gained most (66.67%). The hydroponics program offered real life experiences, reinforced thinking like a scientist, promoted teamwork and nicely built scientific literacy and 21st century skills in students.